Specimen gripping effects in composites fatigue testing -– Concerns from initial investigation - P. B. S. Bailey; A. D. Lafferty (eXPRESS Polymer Letters)
This paper presents the findings of an initial investigation into effects of end tabs and gripping force on specimens for fatigue testing of structural composites. Live measurement of specimen compliance comparing extensometer measurements with grip displacement showed the impact of gripping on the dynamic behavior of the specimen. Use of thermal imaging enabled assessment of how load is introduced and carried along the specimen. The effect of grip pressure and comparative merits of popular solutions are examined in the context of fatigue testing of composites. Although for static tests these potential issues have been investigated extensively throughout the history of composites research, interest has only recently fallen upon their effects on dynamic loading. Data collected show that the gripping pressure at the ends of the specimen can affect results more significantly than may be anticipated. These early results suggest that solutions which are well established for quasi-static testing may cause problems in cyclic tests.